Larval supply of Peruvian scallop to the marine reserve of Lobos de Tierra Island: A modeling approach - Flores-Valiente J. (2019)
The Peruvian scallop (Argopecten purpuratus) is the second main contributor to the total catch of mollusks in Peru, after jumbo squid. There are two main scallop banks populations in northern Peru: Lobos de Tierra Island (LTI) and Sechura Bay (SB). Despite a continuous, intense relocation of seeds from LTI, the natural bank population still persists there. To understand this, we studied larval connectivity between LTI and SB using the first invertebrate larval transport biophysical model developed in the region. Larval local retention were 2.4% and 1.57% on average at LTI and SB respectively, while larval transport from SB to LTI was 0.02% on average and 0.07% in the opposite direction. Both larval retention and larval transport increased with spawning depth and were highest in austral summer. Two main larval transport paths from SB to LTI were identified, resulting from a combination of horizontal mesoscale circulation patterns and vertical flows. Potential management implications for these natural banks are discussed.